Helicobacter pylori y organismos Helicobacter heilmannii-like: ¿qué rol juegan en perros y gatos ? - Váldes, Alicia; Astudillo, Macarena (Avances en Ciencias Veterinarias, 2007)
Helicobacter pylori infection is now recognised as a worldwide problem. It is the most common cause of chronic gastritis, and is strongly linked to peptic ulcer disease and gastric cancer in human patients. In animals, specially in dogs and cats it is still not completely understood. Otherwise, in recent reports there is a new group: Helicobacter heilmannii-like that has been detected in human, canine and feline gastric biopsies; and again it not clear its patologic rol in them. This article rewievs the literature trying to answer the question: Which rol have H. pylori and H. heilmannii -like in dogs and cats?